Estimating the extreme wind speed for regions in China using surface wind observations and reanalysis data. Issue 143 (August 2015) - Mo, H.M.; Hong, H.P.; Fan, F.
Abstract: The exposure category for many meteorological stations in China is temporally varying because of the rapid urbanization and revitalization of cities in last few decades. This causes difficulty in correcting or adjusting the surface wind observations to a standard exposure condition, especially if the information on the temporal changes in the surrounding terrain of the stations is rarely available. This study is to investigate the feasibility of using the temporally varying exposure adjustment factors to process the surface wind observation for extreme value analysis; and to explore the spatial and temporal trends of the extreme wind speed using the NCEP/NCAR Reanalysis 2 data. Extreme value analysis of the annual maximum wind speed V is carried out using the adjusted surface wind observations from about 150 stations. The resulting 50-year return period values of V are employed to develop wind hazard maps of China and are compared with those inferred from the current Chinese design code. The comparison indicates that there is potential to develop new and update the existing wind maps by taking advantage of some of the up to date surface wind observations that are adjusted using temporally varying exposure adjustment factors. Also, the analysis results indicate that the reanalysis data is useful to explore temporal and spatial trends of the extreme wind speeds and to aid the process of developing and updating the wind hazard maps of China. Highlights: Investigated the wind hazard for China using exposure adjusted surface wind observations. Investigated the wind hazard for China using reanalysis data. Compared the developed wind hazard maps with those recommended in Chinese design code. Wind hazard maps developed using surface wind observations and reanalysis data differ.